5cos^6 x+3sin^6 x=1+cos2x

0 голосов
96 просмотров

5cos^6 x+3sin^6 x=1+cos2x


Алгебра (1.7k баллов) | 96 просмотров
Дан 1 ответ
0 голосов

2*cos^2(x) -1 = cos(2x),
cos^2(x) = (1+cos(2x))/2;
1 - 2*sin^2(x) = cos(2x),
sin^2(x) = (1- cos(2x))/2;
левая часть = 5*( (1+cos(2x))/2)^3 + 3*( (1-cos(2x))/2 )^3 = 
 = (1/8)*( 5*(1+cos(2x))^3 + 3*(1-cos(2x))^3 ) = 
 = (1/8)*( 5*(1 + 3*cos(2x) + 3*cos^2(2x) + cos^3(2x) ) +
+ 3*( 1 - 3*cos(2x) + 3*cos^2(2x) - cos^3(2x) ) = 
 = (1/8)*( 8 + cos(2x)*(15 - 9) + cos^2(2x)*(15+9) + cos^3(2x)*(5-3) ) = 
 = (1/8)*( 8 + 6*cos(2x) + 24*cos^2(2x) + 2*cos^3(2x) ) = 
 = (1/4)*( 4 + 3*cos(2x) + 12*cos^2(2x) + cos^3(2x) ) = 1+cos(2x),
4+ 3*cos(2x) + 12*cos^2(2x) + cos^3(2x) = 4 + 4*cos(2x),
cos^3(2x) + 12*cos^2(2x) - cos(2x) = 0;
cos(2x)*( cos^2(2x) + 12*cos(2x) - 1 ) = 0;
cos(2x) = 0; или cos^2(2x) + 12*cos(2x) - 1 = 0;
1) cos(2x) = 0; <=> 2x = (п/2) + п*n, n - целое число.
x = (п/4) + (п/2)*n, n-целое число.
2) cos(2x) = y,
-1<=y<=1;<br>y^2 + 12*y - 1 = 0;
D/4 = 6^2 + 1 = 37,
y1 = (-6+V(37));
y2 = (-6-V(37))<-1; y2 не годиться.<br>0<(-6+V(37)),<br>(-6+V(37))<1; <br>V(37)<7,<br>37<49, верно.<br>cos(2x) = (-6+V(37)).

0

Cos^4 x-cos^2 x * sin^2 x + sin^4 x=4cos^6 x + 2sin^6 x - cos^2 x + cos П/3? а с этим не поможете? он есть в заданных вопросах

0

8cos x=sec x + √3 * csc x и еще...)))